148 Effect of Increasing Sodium Sulfate in Water on Intake on Ruminal Fermentation and the in Vitro Effect of Bismuth Subsalicylate on gas Production and NDF Digestibility. (21st September 2022) - Evans, Mikaela G; Ribeiro, Gabriel O; Henry, Darren H; Johnson, Jordan A; Campbell, John R; Waldner, Cheryl; Penner, Gregory B
Abstract: This study evaluated in vivo effects of increasing sulfate concentrations of drinking water on dry matter intake (DMI), water intake, ruminal fermentation, and apparent total-tract digestibility, and in vitro effects of water sulfate and bismuth subsalicylate (BSS) dose. Eight ruminal-cannulated beef heifers (382 ± 45 kg) were stratified into two complete and one incomplete 3×3 Latin squares with 28 d periods. Water contained 341 ± 29 (LS), 2, 785 ± 71 (MS), or 4, 948 ± 163 mg/L (HS) sulfate. Feed and water intake, ruminal fermentation, and nutrient digestibility were evaluated. Ruminal gas samples were collected every 4 h on d 27 to analyze hydrogen sulfide (H2 S) concentration. At the end of each period, digesta collected from heifers in the complete Latin squares were used for in vitro incubation to evaluate water sulfate and BSS dose (0.0, 0.2, 0.4, and 0.6% dry matter). Water intake was 7 L/d greater (P < 0.01) for HS than LS, while MS did not differ. Water sulfate did not affect DMI, but total sulfur intake increased with increasing water sulfate concentration (P < 0.01). Heifers drinking MS and HS had greater ruminal H2 S for 10.5 h after water provision and HS continued to be greater for another 4 h relative to LS (sulfate hour, P < 0.01). Ruminal SCFA concentration, molar proportions of major acids, and nutrient digestibility were not affected (P≥0.19). There were no interactions between water sulfate and BSS in vitro. In vitro H2 S production (µg/48 h) increased with increasing sulfate concentration (P < 0.01) and was reduced (P=0.05) by BSS inclusion. Neutral detergent fiber digestibility was not affected by sulfate or BSS. Increasing water sulfate concentrations did not negatively affect water or feed intake but did increase H2 S concentration and production in vivo and in vitro, respectively. Bismuth subsalicylate may be a potential strategy to reduce H2 S production.